Customer Retention Management Strategies in Freight Transport Service Industry in Ghana. - Ofori-Okyere, Isaac; Atanga, Renas Ayebono (Archives of Business Research, 2016)
This paper reviewed both theoretical and empirical literature on why customers defect in businesses, and roles played by Freight Transport firms to adopt customer retention management strategies to achieve their corporate goals. This paper seeks to explore variables, which may be considered in any Customer Retention Management Strategy and Customer Retention by drawing together strands from various literature on: Strategies and analytical approaches for managing customer defections; Customer defection groups, reasons for their defections, and the role of Life Time Value of Customer (LTVC); Models that can be adopted to manage customer defections and to promote retention; and Factors that constitute actual switching barriers. It is found that freight transport businesses like other services can and should put in place proven marketing strategies to monitor and lessen customer defections. Specifically, freight transport firms in Ghana need to modify their business philosophies by focusing on those customers who leave instead of spending huge costs to attract prospects purposely to replace existing ones.